If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(4g + 3) = -24 Reorder the terms: 4 + -1(3 + 4g) = -24 4 + (3 * -1 + 4g * -1) = -24 4 + (-3 + -4g) = -24 Combine like terms: 4 + -3 = 1 1 + -4g = -24 Solving 1 + -4g = -24 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4g = -24 + -1 Combine like terms: 1 + -1 = 0 0 + -4g = -24 + -1 -4g = -24 + -1 Combine like terms: -24 + -1 = -25 -4g = -25 Divide each side by '-4'. g = 6.25 Simplifying g = 6.25
| 4x=52-(x+7) | | -3x-3(-3-3x)=9+6x | | 64-(3x-4)=x | | -(2k-1)=7 | | 3x+140=4x | | 14x=x+169 | | 20+(4x-6)=6x | | 70-(2x+5)=3x | | 90+2x=4x | | 4x=72-2x | | 90=4x-(2x-6) | | 3x-(x+14)=180 | | 7x^2+10q=2q^2+155 | | 4x+(x+25)=90 | | 9x+6=15x+6 | | 17=x+9 | | 8(x+4)=1+8x | | 5x+2(3x+8)=5 | | 5x+72=9(x+8)-4x | | 17=y+0 | | -6+6= | | 3n+7=2n-1 | | 3x+4-2x-8=5+4x | | 6x^2-8x-3=0 | | 6x+7=6x-7 | | .833y=.33(y+6) | | 106+(x+5)+x+135+94=540 | | .5(x+18)=19 | | 15x^2-16x-8=0 | | 2(3.4)+v=-16 | | ax^2-(2a+1)x+(a+1)=0 | | 5u+3v=-16 |